Developing Podcast-Based Learning Media for English Education Among Deaf Students - Yuniarti, Fatma; Pratiwi, Dian; Novianto, Robi (VELES Voices of English Language Education Society, 2024)
This study addresses the educational challenges faced by deaf students in Indonesia, focusing on developing and implementing a specialised Android-based application, "PODclusive," to facilitate English language learning. The research aimed to create an interactive learning tool that incorporates sign language and textual translations in both English and Indonesian, tailored to the needs of deaf learners. The methodology was a mixed-method approach, combining qualitative and quantitative analyses. The research and development (R&D) framework guided the application's design, development, and evaluation. Participants included a purposive sample of 30 deaf students from SLB N Pringsewu, ensuring a representation across different learning outcomes. The findings revealed that the PODclusive application significantly enhanced the learning experience for deaf students. Students demonstrated improved comprehension of English language concepts, facilitated by the application’s use of sign language video content and offline accessibility. The application was evaluated through expert reviews and user testing, receiving high validity scores for content, design, and educational impact. The implications of this study underscore the effectiveness of tailored educational technologies in addressing specific learning needs. The PODclusive application exemplifies how digital tools can enhance accessibility and engagement for deaf students, suggesting that further exploring similar technologies could be beneficial. This research contributes to the broader discourse on inclusive education, advocating for more innovative approaches to support diverse learning environments.